2011
DOI: 10.1037/a0026238
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated deficits in pattern separation functions of the perirhinal cortex: A cross-species consensus.

Abstract: Normal aging causes a decline in object recognition. Importantly, lesions of the perirhinal cortex produce similar deficits and also lead to object discrimination impairments when the test objects share common features, suggesting that the perirhinal cortex participates in perceptual discrimination. The current experiments investigated the ability of young and aged animals to distinguish between objects that shared features with tasks with limited mnemonic demands. In the first experiment, young and old rats p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
123
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 64 publications
28
123
0
Order By: Relevance
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 80%
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 80%
“…In support of this interpretation, discrimination abilities are impaired in healthy aged humans (Toner et al 2009;Stark et al 2010Stark et al , 2013Holden et al 2012Holden et al , 2013Ryan et al 2012;Reagh et al 2014Reagh et al , 2016, monkeys (Burke et al 2011), and rats (Burke et al 2010(Burke et al , 2011). An intriguing aspect of these deficits is that older adults who do not show episodic memory loss can be impaired relative to young adults at difficult discriminations between similar stimuli, but not easy discriminations between unique stimuli (Stark et al 2013;Reagh et al 2014Reagh et al , 2016.…”
mentioning
confidence: 73%
“…Parallel observations have been made in animal models of aging. Aged rats are impaired in spatial memory (Gallagher et al 1993;Bizon et al 2009;McQuail and Nicolle 2015), in discriminating between novel and familiar stimuli (Burke et al 2010(Burke et al , 2011, and in place learning when the learned target location is in close proximity to a foil location (Gracian et al 2013).…”
mentioning
confidence: 99%
“…Thus, it is difficult to evaluate the degree of dissimilarity and the difficulty level of the discrimination. This can be critical because ambiguity and complexity features have been proposed as essential variables determining SOR deficits in aged rats (Burke et al 2010(Burke et al , 2011 and in adult PER lesioned rats (Buckley and Gaffan 1998;Eacott et al 2001;Norman and Eacott 2004;Bartko et al 2007a,b). In fact, the role of ambiguity in SOR performance has often been evaluated in configural tasks using complex objects (Bartko et al 2007a(Bartko et al , 2010.…”
mentioning
confidence: 99%
“…Since subtle modifications of the object's features in SOR tasks has proven to be relevant for involving different brain areas such as PER cortex (Ennaceur and Aggleton 1997;Eacott et al 2001;Murray and Richmond 2001;Norman and Eacott 2004;Winters et al 2004;Winters and Bussey 2005b;Bartko et al 2007aBartko et al , 2010Cowell et al 2010), a precise description is included. In this respect, it has been suggested that SOR memory impairments in aged rats could be related to PER dysfunction (Burke et al 2010(Burke et al , 2011. There is some controversy about the brain areas involved in stimulus recognition both in rodents and primates (Mishkin 1978;Zola-Morgan et al 1982;Saunders et al 1984;Clark et al 2000;Zola et al 2000;Broadbent et al 2004).…”
mentioning
confidence: 99%